KORELASI ANTARA BRACHIAL-ANKLE PULSE WAVE VELOCITY DAN PROFIL LIPID PADA KARYAWAN RUMAH SAKIT SANGLAH DENPASAR - Arsana, Gede Putu; -, Kambayana; Santoso, Anwar; Suastika, Ketut (journal of internal medicine; Vol. 8, No. 2 Mei 2007, 2012)
Brachial-ankle pulse wave velocity (baPWV) is an indicator of limb arterial stiffness. Dislipidemia is a major risk factor of atherosclerosis and may worsen baPWV by increasing the blood viscosity. This study aims to study the correlations between baPWV and the lipid profile among employees of Sanglah Hospital. Cross sectional analytic study was performed in Sanglah hospital. Pulse wave velocity was measured using an automatic device (Fukuda VS 1000). Lipid profile were taken as well. Data was expressed in mean + SD, analyzed by t-test compare mean and Pearson correlation by using SPSS 13.0. There were 85 patients involved, all subjects were male, age all between 40-56 (mean 47.23 + 5.16) years old. Cholesterol total, LDL-C, HDLC, and triglyceride concentrations varied subject, range (means + SD) as (205.05 + 39.40) mg/dL, (144.26 + 36.85) mg/dL, (45.94 + 8.98) mg/dL, and (151.94 + 64.56) mg/dL, respectively. BaPWV on the right limbs were between (13,31 + 2,14 ) m/sec, on the left limbs were (15,05 + 2,33 ) m/sec. Significant correlations were found between total cholesterol concentration and the left baPWV (r = 0.222, p = 0.41), while a significant correlation were found on the right side (r = 0.234, p = 0.031). Brachialankle pulse wave velocity is positively correlation with total cholesterol concentration.
Keywords: Brachial-ankle Pulse Wave Velocity (baPWV), profil lipid